Pengaruh Komposisi Biopotting Terhadap Pertumbuhan Sengon Laut (Paraserianthes Falcataria L. Nietsen) Di Persemaian - Nursyamsi; Hermin Tikupadang (Foresty Faculty of Hasanuddin University, 2014)
To support the growth of sengon laut optimal seeding in the field, it is necessary to have seed quality. Quality seedlings in the nursery are directly influenced among others by the condition of the growing medium. Biopotting is a pot growing medium made of compost derived from organic ingredients and blended with beneficial soil microbes eg mycorrhizae. This study aims to determine the optimal composition biopotting for seedling growth sengon laut (Paraserianthes falcataria L.Nielsen) for three months in the nursery. Experimental design used was completely randomized design with treatment composting saw dust 70% + clay 30%+ Mycorrhiza (S7T3M), sawdust compost 70% + clay 30%+ Without Mycorrhiza (S7T3TM), sawdust compost 80% + clay 20%+ Mycorrhiza (S8T2M), sawdust compost 80% + clay 20% +Without Mycorrhiza (S8T2 TM), kerinyu compost 70 % +clay 30%+ Mycorrhiza (K7T3 M), kerinyu compost 70% + clay 30% + Without Mycorrhiza(K7T3TM), kerinyu compost 80% + clay 20% + Mycorrhiza (K8T2M) and kerinyu compost 80%+ clay 20%+ without Mycorrhiza(K8T2TM). Biopotting formulations made from sawdust compost 70% + clay 30% + Mycorrhiza FMA (S7T3M) has added 9.49 cm tall seedlings, stem diameter 1.802 mm and seedling quality index is 0.3908. To support the growth of sengon laut optimal seeding in the field, it is necessary to have seed quality. Quality seedlings in the nursery are directly influenced among others by the condition of the growing medium. Biopotting is a pot growing medium made of compost derived from organic ingredients and blended with beneficial soil microbes eg mycorrhizae. This study aims to determine the optimal composition biopotting for seedling growth sengon laut (Paraserianthes falcataria L.Nielsen) for three months in the nursery. Experimental design used was completely randomized design with treatment composting saw dust 70% + clay 30%+ Mycorrhiza (S7T3M), sawdust compost 70% + clay 30%+ Without Mycorrhiza (S7T3TM), sawdust compost 80% + clay 20%+ Mycorrhiza (S8T2M), sawdust compost 80% + clay 20% +Without Mycorrhiza (S8T2 TM), kerinyu compost 70 % +clay 30%+ Mycorrhiza (K7T3 M), kerinyu compost 70% + clay 30% + Without Mycorrhiza(K7T3TM), kerinyu compost 80% + clay 20% + Mycorrhiza (K8T2M) and kerinyu compost 80%+ clay 20%+ without Mycorrhiza(K8T2TM). Biopotting formulations made from sawdust compost 70% + clay 30% + Mycorrhiza FMA (S7T3M) has added 9.49 cm tall seedlings, stem diameter 1.802 mm and seedling quality index is 0.3908.